Improving Educational Quality through Optimizing the Potential of Educational Institutions in Indonesia - Ismail, Feiby; Daeng Pawero, Abdul Muis; Umar, Mardan (CV. Inara, 2021)
The quality of education in an educational institution will be greatly influenced by the potential of educational institutions and the governance system. The existing potential must be optimized to support quality improvement. Likewise, the education governance system will develop well when it is implemented through a good system by professional managers. The system has been designed in detail by the government which was stipulated by the Minister of National Education Regulation No. 19 of 2007 concerning